Pengaruh Metode Three Step Interview terhadap Hasil Belajar Sejarah Siswa MA Al-Islamiyah Bebidas Lombok Timur - Wulandari, Rulia; Rasyad, Abdul; Suhupawati, Suhupawati (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2021)
The purpose of this study was to determine the effect of the Three Step Interview method on student history learning outcomes. The research method used is an experimental method. The experimental design used was quasi-experimental by giving treatment in the form of applying the Three Step Interview method to the experimental class and the conventional method to the control class. The sample in this study amounted to 35 people. The data collection technique used was a multiple choice test, while the data analysis technique used was the t test using SPSS 16.0. Based on data analysis, the significance value of the t-test for Equality of Means was 0,000 0.05. These results indicate that there is a positive and significant influence of the Three Step Interview method on student history learning outcomes.